2016
DOI: 10.5966/sctm.2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Human Cortical Neural Stem Cells Expressing Insulin-Like Growth Factor-I: A Novel Cellular Therapy for Alzheimer's Disease

Abstract: A human cortex-derived neural stem cell (NSC) line modified to express insulin-like growth factor-I (IGF-I), HK532-IGF-I, is characterized in this report. The cell line is under study as a cellular therapy for Alzheimer’s disease (AD). HK532-IGF-I cells preferentially differentiated into gamma-aminobutyric acid-ergic neurons, a subtype dysregulated in AD; produced increased vascular endothelial growth factor levels; and displayed an increased neuroprotective capacity in vitro. HK532-IGF-I cells survived peri-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 92 publications
2
69
2
Order By: Relevance
“…30 In a more recent study, a human cortex-derived neural stem cell line modified to express IGF-1 was shown to exhibit neuroprotective capacity in vitro and persists in targeted brain regions in an animal model of AD. 54 In studying the molecular mechanism of IGF-1, we have found that IGF-1 increased the SUMOylation of HDAC1 in rat hippocampus. This result suggests that HDAC1 SUMOylation is a novel mechanism underlying the neuroprotective action of IGF-1.…”
Section: Discussionmentioning
confidence: 96%
“…30 In a more recent study, a human cortex-derived neural stem cell line modified to express IGF-1 was shown to exhibit neuroprotective capacity in vitro and persists in targeted brain regions in an animal model of AD. 54 In studying the molecular mechanism of IGF-1, we have found that IGF-1 increased the SUMOylation of HDAC1 in rat hippocampus. This result suggests that HDAC1 SUMOylation is a novel mechanism underlying the neuroprotective action of IGF-1.…”
Section: Discussionmentioning
confidence: 96%
“…Male Tg‐AD B6C3‐Tg(APPswe/PSEN1ΔE9)85Dbo/J (APP/PS1) mice were obtained from the Jackson Laboratory (Bar Harbor, ME). Research grade human NSCs, NSI‐HK532‐IGF‐I, a modified line we previously characterized,15 were provided by Neuralstem, Inc. (Germantown, MD). NSCs were administered to 12‐week‐old mice by three injections into the CC bilaterally at three sites (total six injections), represented by the following atlas coordinates from the bregma (posterior, lateral, ventral): −0.82/(±)0.6/1.9, −1.82/(±)0.6/1.5, −2.3/(±)0.6/1.5 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…IGF-I expression has been found in neural stem cells derived from fetal human forebrains [57], and most likely it is induced by GH in the human adult brain [58]. The IGF-I receptor (IGF-IR) maintains a stable expression in the brain throughout life, at least in rats [59], but it is likely that it also occurs in human adults to bind to free IGF-I, which reaches the brain from plasma [60].…”
Section: Discussionmentioning
confidence: 99%